Pathogenetic Rationale for the Selection of Mucolytics with Multidirectional Action in the Treatment of Respiratory Diseases in Children - O.Ye. Chernyshova (Zaslavsky O.Yu., 2015)
Violations of mucociliary clearance accompany any damage of the respiratory system. The paper presents the pathogenetic mechanisms of changes developing at this time and their consequences. The methods to recover airway clearance processes on the background of using acetylcysteine, mucolytic with complex effects, were considered.